(untitled) (Brazilian Journal of Health Research, 2019)
Introduction: Most studies on this subject have focused on the close association between social and health inequalities. Objective: Reviewing social inequalities in health observed in the last three decades based on empirical research carried out in Loures County, Lisbon Metropolitan Area, Portugal. Methods: The study focused on the population in the age group 18 years, or older, living in Loures County. We adopted a quantitative method and applied a survey to a representative sample, which was stratified by sex, age and residence area. In total, 1,100 surveys were conducted through interviews performed in all country districts. Results: Based on the results, strong differences between social classes concerned several factors such as the kind of access to health services (public / private), dental consultations and preventive practices such as weight control or food consumption. On the other hand, we observed transversal practices to different social classes, for example, regular attendance in medical consultations and examinations mostly due to universal access to public health services. The same relative transversality among social class trends was observed in regular medication intake. Conclusion: In-depth studies on the association between social and health inequalities can be essential to support the implementation of sustainable social lines and political interventions.